Chief Executive Officer, Financial Leverage dan Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia - Ramadana, Sri Winarsih; Mariana, Mariana (Prodi Hukum Ekonomi Syariah, STI Syariah AL-Hilal SIgli, 2023)
The purpose of this study is to determine the influence of the chief executive officer's gender and experience of the chief executive officer in influencing financial leverage on manufacturing companies listed on the Indonesia Stock Exchange in 2017-2021. The data analysis method in this study uses multiple linear regression to predict the influence of independent variables. The population in this research is a manufacturing company listed on the Indonesia Stock Exchange from 2017 to 2021. The sampling method in this study is the purposive sampling method. The results showed that the CEO gender affects financial leverage. This means that the gender of a CEO has a significant relationship with the use of debt. And the CEO's experience does not affect financial leverage. Because CEOs are more likely to use funds from debt and do not carefully consider their decision to use the debt.